2022
DOI: 10.1002/mnfr.202100784
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Blueberry Ameliorates Vascular Complications in Diabetic Mice Possibly through NOX4 and Modulates Composition and Functional Diversity of Gut Microbes

Abstract: Scope: In diabetes, endothelial inflammation and dysfunction play a pivotal role in the development of vascular disease. This study investigates the effect of dietary blueberries on vascular complications and gut microbiome in diabetic mice. Methods and Results: Seven-week-old diabetic db/db mice consume a standard diet (db/db) or a diet supplemented with 3.8% freeze-dried blueberry (db/db+BB) for 10 weeks. Control db/+ mice are fed a standard diet (db/+). Vascular inflammation is assessed by measuring monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…As described above, the gut microbiota is an important player in the physiology and pathology of DM. Therefore, many animal and clinical experiments are conducted to explore preventive and therapeutic strategies for DM that target the gut microbiota. − Meaningfully, some foods and herbal medicines have been shown to have beneficial uses for different types of DM. − They contain abundant natural products and exert antidiabetic effects by improving the intestinal microecological environment (Figure ).…”
Section: Natural Products Targeting the Gut Microbiota In Dmmentioning
confidence: 99%
“…As described above, the gut microbiota is an important player in the physiology and pathology of DM. Therefore, many animal and clinical experiments are conducted to explore preventive and therapeutic strategies for DM that target the gut microbiota. − Meaningfully, some foods and herbal medicines have been shown to have beneficial uses for different types of DM. − They contain abundant natural products and exert antidiabetic effects by improving the intestinal microecological environment (Figure ).…”
Section: Natural Products Targeting the Gut Microbiota In Dmmentioning
confidence: 99%
“…Rodriguez-Mateos et al 89 previously demonstrated acute blueberry consumption reduced neutrophil NADPH oxidase activity which was associated with increased FMD in healthy men. In diabetic db/db mice, Petersen et al 90 showed that blueberry consumption for 10 weeks improved endothelial function through reductions in NADPH oxidase 4 gene expression in aortic vessels and vascular endothelial cells. Several investigators have explored the effects of blueberry consumption on biomarkers of oxidative stress and antioxidant defense, and reported results have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Mateos et al 89 previously demonstrated acute blueberry consumption reduced neutrophil NADPH oxidase activity which was associated with increased FMD in healthy men. In diabetic db/db mice, Petersen et al 90 showed that blueberry consumption for 10 weeks improved endothelial function through reductions in…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Additionally, microbial hydrolases act on the anthocyanidins to produce metabolites such as phenolic acids which are more easily absorbable. [ 15 ] Blueberry bioactive components are extensively metabolized by intestinal microbiota in humans suggesting that microbiota‐induced metabolites might mediate the health beneficial effects of dietary blueberry. [ 15 ] Studies from our lab and others indicate that dietary blueberries impact gut health by improving gut dysbiosis.…”
Section: Introductionmentioning
confidence: 99%